Analisis Return On Assets (ROA) dan Return On Equity Terhadap Rasio Permodalan (Capital Adequacy Ratio) Pada PT Bank Sinarmas Tbk - Rani Kurniasari (Universitas Bina Sarana Informatika, 2017)
A Company always strives to obtain maximum results by using the capital they have optimally including in banking activities. The health of a bank can be seen from the use of its capital to generate profit after tax.In this study the authors use the quantitative method that is through the financial statements in the if own. Analyzer used in this research is Multiple Linear Regression using IBM SPSS Statistics 22 application.The financial statements used are the tube financial statements in 2011 until 2015. The calculation result show between ROA and ROE to CAR simultaneously exist a very strong relationship of 0.935. Between ROA and ROE to CAR simultaneously there is a significant influence or contribution by 87%. The multiple regression equation that is formed is Y=13,971+11,717X1-1,248X2Keyword : ROA, ROE, CAR